Analisa Kualitatif Kandungan Merkuri dalam Sediaan Pemutih Kulit yang Dijual di Online Shop - Ni Kadek Mita Pratiwi Nugraha; Dyah Angraeni (STIKes Surya Global Yogyakarta, 2019)
Background: Mercury (Hg) is used illegally in cosmetics as a whitening or skin lightening agent because of its ability to inhibit melanin formation on the surface of the skin. Mercury can make white skin smooth in a relatively short time, but this substance has a negative effect on health because it can accumulate in the body. This is because mercury that enters the human body is not easily excreted. This mercury can accumulate in the human body especially in the kidney, liver and brain organs.Objective: This study is aimed to find out whether mercury is sold in skin whitening product by Online Shop.Methods: This research was a descriptive study by using the color reaction test method. The samples in this study were 6 samples taken from the Online Shop. The sampling technique in this study used a purposive sampling technique. The procedure of the color reaction test was the sample is weighed 2 grams and then added 25 ml of mineral water and 10 ml of mineral water, then evaporated until it was almost dry. At the last evaporation added 10 ml mineral water. Then it was heated for a while, cooled and filtered. The next step on Potassium Iodide was 0.5 N 1 ml of sample solution put into a test tube and then add 2 drops of Potassium Iodide slowly through the tube wall, if there was a change in the color of orange with precipitate, then the positive reaction contains mercury.Results: This study showed that the six samples of non-facial skin whitening products which is sold in the Online Shop obtained three positive samples containing mercury, due to an orange discoloration with sediment and three samples containing negative mercury.Conclusion: There were three positive samples containing mercury marked by an orange discoloration in skin whitening purchased by Online Shop.Keywords: Mercury, Skin whitening products, Color reactions.